Significant of teritorry to increase sense of place in behavioural settlements - Hero Farkisch,; Vahid Ahmadi,; Adi Irfan,; Mastor Surat,; M. Fauzi M. Zain, (Journal of Faculty of Social Sciences and Humanities. Universiti Kebangsaan Malaysia, 2009)
Cities have transformed collecting public places into private spaces. While in the past, public places as an urban place had a specific identity for themselves. Nowadays in nonexistence of connection between public and private life residents are forced to create their social life within their own control and are not entered to identity in public space. Urban spaces are made regardless to social needs of residents and their cultural origins. Formation of urban spaces impact to quality of its social and spatial and cannot be absorbed potential of environmental and social. For reproduction of social identity is required the behaviour-milieu this behaviour-milieu is a place for standing of pattern behaviour. In this way the role of neighborhood center as behavioural setting appears to be helping as to establish the distinctive identity of the place and create the conditions in which residents can develop their relationships and control. Behavioural complex also provide context of social partnership. Places can be considered as a physical form with their spatial territory which supports activity, ceremonies, and events and helps to sense of place formation. Feeling of neighborhood territory will exacerbate dependence and sense of place to it. The most important aspect of sense of place is attachment of people to their home or neighborhood sphere. Belonging to them make a territory feeling. Sense of place supports the cultural concept, social and culture relationship of society in the place and achieves to individual identity. This paper reviews recent research and literature review into the concept of sense of place and their assessment. The aim of this study was to evaluate the sense of place in the traditional urban to be carried out in the contemporary urban setting. The discussion presents the relationship between four groups of sense of place, territory, dependence, and finally provides a conceptual model as to show how these factors affect to sense of place. The result of this study indicates a model that mentions a relationship between dimensions of sense of place. This paper argues that territory in behavioural setting as the subset of place dependence is the best instrument to improve the sense of place